口腔鳞状细胞癌组织中差异微小RNA/mRNA表达谱的对接研究 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2014)
OBJECTIVE: To construct and analyze the differential expression profiles of microRNAs (miRNA) and mRNA in oral squamous cell carcinoma (OSCC). To explore the miRNA and mRNA of OSCC development and progression. METHODS: The differential expression profiles of miRNA and mRNA were built by high-throughput deep sequencing technology. Using Gene Ontology (GO) enrichment analysis, the roles of differentially expressed miRNA and mRNA in cell cycle, cell proliferation, cell differentiation and cell apoptosis were analyzed. RESULTS: Seventy-seven differentially expressed miRNA and 1 298 differentially expressed mRNAs were identified in OSCC. GO analysis showed that 73 miRNA had found target mRNA in cell cycle, cell proliferation, cell differentiation and cell apoptosis of OSCC. Moreover, a miRNA could regulate multiple mRNA. CONCLUSION: The differential expression profiles of miRNA and mRNA have close relationship with the development and progression of OSCC.